Экспериментальные исследования моделей высоконапорных пеногенераторов (эжекторов-смесителей) проточного типа, работающих в кавитационном режиме. Выбор оптимального параметра кавитации, расчет пределов кавитации и потерь давления - Parmon, Валерий (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2010)
The work presents the research results of the process of cavitation origin and development in foam generators (ejector-mixers), based on the construction of the Venturi tube, under different flow conditions, as well as the results on determination of the optimal design and size for foam generators (ejector-mixers) in order to obtain in them the peak development of cavitation flow with minimal hydrodynamic resistance and maximal back-pressure in the system at the output from foam generators (ejector-mixers). The methods to choose the optimal parameters of cavitation, as well as the calculation of the cavitation limits and pressure loss are given.